Analisis terhadap Kesulitan Belajar Mahasiswa Teknik Informatika pada Mata Kuliah Kalkulus - Welly Desriyati; Hanifatul Rahmi (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2021)
This article was a qualitative research with using phenomenology approach. The researchers were the main research instruments in this study in order to analyze the type of informatics engineering studenet’s learning obstacles in calculus subject, its causative factors and the ways to overcome the students’ learning obstacles. Researcher as the lecturer used test, questionnaire, observation sheet and interview technique to collect the data. The subject of this study was 47 students of informatics engineering study programme, while the object of this study was the students’ learning obstacles. According to the data analysis results, the findings of this study are: (1) the type of informatics engineering studenet’s learning obstacles in calculus subject are in the principle, concept, operation and fact; (2) the causative factors of informatics engineering students’ learning obstacles in calculus subject are: less using of learning media, using incorrect methods, less of study needs, the lowerness of students’ intelligence, the lowerness of students’ motivation in learning mathematics and the lowerness of students’ prior mathematical knowledge; and (3) to overcome the informatics engineering students’ learning obstacles in calculus subjectare: rearrange learning schedule at home, give guidance to the students, using variatif methods, using clear learning methods and multiplicate the supportive learning facilities.